PENGEMBANGAN BAHAN AJAR INOVATIF UNTUK SISWA SMA POKOK BAHASAN STRUKTUR ATOM DAN TABEL PERIODIK UNSUR - Devi Anriani Siregar; Iis Siti Jahro; Ramlan Silaban (Jurnal Pendidikan Kimia (JPKim), 2015)
Abstract This study aimed to obtain an character base-innovative teaching module on teaching atomic structure and periodical table of element contain character base education. This type of research is a research and development modified from Borg-Gall methods. The 20 teachers chemistry of X grade class of SMA (senior high school) used as samples  or responden to analysing chemistry textbook produced by two publisher using BSNP (National Education Standards Agency) instrument standard. The results show that both of textbook contain atomic structure and periodical table of element have good quality but it possible to developed to get an innovative teaching module which revise in subject matter sequences and teaching strategy. The innovative teaching module received had been fully BSNP standard, quite valid,  feasible and does not need to be revised. From trial using quasy experiment methods show that student outcomes  thought using innovative teaching module (average 88.5) higher than control class (average 80.75). Keywords: Research and Development, Atomic Structure and the Periodic Table, character education, Curriculum 2013.